Everything is Going Electronic, so do Services and Service Quality: Bibliometric Analysis of E-Services and E-Service Quality - Ali, Javed; Jusoh, Ahmad; Idris, NorHalima; Abbas, Alhamzah F.; Alsharif, Ahmed H. (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The purpose of the study was to explore the developments in ‘e-services and e-service quality’ from 2000 to 2020. Data Source: Scopus database was used to conduct the bibliometric analysis of 404 documents. Method: VOSviewer soft-ware was used to analyse the research articles associated with ‘e-services and e-service quality’ research. Search was limited to keywords of ‘e-services OR e-service and e-service quality’. Findings: Results revealed that the field of ‘Busi-ness, Management and Accounting’ had the highest number of publications. To-tal Quality Management and Business Excellence was found at the top among the most productive journals in chosen search. Chang W.-I. and Yuan S.-T. from Taiwan were found to be the leading authors among top ten authors. United States and National Cheng Kung University of Taiwan were found to be the lead-ing country and institution in the selected search of e-service and e-service quali-ty. Originality/ Value: This study, to best of our knowledge, is the first of its kind in mapping the ‘e-services and e-service quality’ literature in Scopus. This will aid in shaping the central theme and set the future research directions for the researchers.